Influence of Grain Size Evolution on Mantle Plume and LLSVP Dynamics - Yusen Liu; Ting Yang; Kai Wang; Xiong Wang; Yang Li (Geochemistry, Geophysics, Geosystems)
Abstract Recent seismic tomography models suggest large‐radius primary plumes originating from the core‐mantle boundary, with grain size variations potentially explaining these observations. Additionally, grain size variations are thought to enhance the long‐term stability of Large Low Shear Velocity Provinces (LLSVPs), identified as thermochemical piles near the core‐mantle boundary. Nevertheless, geodynamic models investigating these hypotheses remain limited. To address this gap, we constructed a series of geodynamic numerical models incorporating grain size evolution, plate tectonics, and the spontaneous generation of deep mantle plumes above LLSVPs. Our results reveal that grain size evolution does not significantly affect the plume width, primarily because the increased strain rate in the mantle plume suppresses both its grain size and viscosity. The region adjacent to the plumes, characterized by the accumulation of mantle materials with larger grain size and low‐temperature remnants of subducted slabs, displays a higher viscosity compared to the area near the subducted slabs. Furthermore, grain size evolution plays a crucial role in enhancing the stability of LLSVPs by increasing the viscosity ratio between LLSVPs and the ambient mantle. These findings underscore the need for incorporating grain size evolution in geodynamic models to gain a better understanding of the dynamics of plumes and lower mantle.